PENGARUH PROFIL PETANI PENGELOLA AGROWISATA TERHADAP KAPASITAS PEMANFAATAN TEKNOLOGI KOMUNIKASI DIGITAL DI KABUPATEN BOJONEGORO DAN MALANG, PROVINSI JAWA TIMUR - Lestari, Niken; Amanah, Siti; Muljono, Pudji; Susanto, Djoko (AGRARIS: Journal of Agribusiness and Rural Development Research, 2019)
Digital communication technology provides wider opportunities for agritourism farmers to reach local and national markets. Agritourism as a diversification of agricultural business encourages farmers to have the capacity to utilize digital communication technology. This study aims to (1) identify the profile of farmers who managing agritourism and (2) analyze the influence of farmer profiles on the level of capacity to use digital communication technology. The profile of agrotourism farmers influences their capacity to use digital communication technology in response to economic changes. The study was conducted in Bojonegoro and Malang Regencies, East Java in September and October 2018. Data collection was conducted through interviews using questionnaires on 215 farmers. Data analysis was analyzed using descriptive and inferential statistics. The result of the study showed that the farmer profile which includes age, the level of formal education and the assessment of digital technology functions were categorized as high. Business motivation was in medium category while nonformal education, length of business, types of agritourism products and cosmopolitan level were in low category. The types of agritourism services was in very low category. The result of analysis showed the profile of agritourism farmer that has a very significant effect to increase the capacity of farmers to utilize digital communication technology were age, formal education, assessment of digital communication technology functions, and business motivation, while having a significant effect are non-formal education, length of business, and agritourism products.